Quantifying gender disparity in physician authorship among commentary articles in three high-impact medical journals: an observational study. Issue 2 (25th February 2020) - Mamtani, Mira; Shofer, Frances; Mudan, Anita; Khatri, Utsha; Walker, Rachael; Perrone, Jeanmarie; Aysola, Jaya
Abstract : Background: Scholarship plays a direct role in career advancement, promotion and authoritative recognition, and women physicians remain under-represented as authors of original research articles. Objective: We sought to determine if women physician authors are similarly under-represented in commentary articles within high-impact journals. Design/Setting/Participants: In this observational study, we abstracted and analysed author information (gender and degree) and authorship position from commentary articles published in three high-impact journals between 1 January 2014 and 16 October 2018. Primary outcome measure: Authorship rate of commentary articles over a 5-year period by gender, degree, authorship position and journal. Secondary outcome measures: To compare the proportion of men and women physician authorship of commentaries relative to the proportion of men and women physician faculty within academic medicine; and to examine the gender concordance among the last and first authors in articles with more than one author. Results: Of the 2087 articles during the study period, 48% were men physician first authors compared with 17% women physician first authors (p<0.0001). Of the 1477 articles with more than one author, similar distributions were found with regard to last authors: 55% were men physicians compared with only 12% women physicians (p<0.0001). The proportion of women physician first authors increased over time; however, the proportion of women physician last authors remained stagnant. Women coauthored with women in the first and last authorship positions in 9% of articles. In contrast, women coauthored with men in the first and last author positions, respectively, in 55% of articles. Conclusions: Women physician authors remain under-represented in commentary articles compared with men physician authors in the first and last author positions. Women also coauthored commentaries with other women in far fewer numbers.